Metabolic control and sex: A focus on inflammatory‐linked mediators. (21st April 2019) - Henstridge, Darren C.; Abildgaard, Julie; Lindegaard, Birgitte; Febbraio, Mark A.
Abstract : Men and women have many differing biological and physiological characteristics. Thus, it is no surprise that the control of metabolic processes and the mechanisms underlying metabolic‐related diseases have sex‐specific components. There is a clear metabolic sexual dimorphism in that up until midlife, men have a far greater likelihood of acquiring cardio‐metabolic disease than women. Following menopause, however, this difference is reduced, suggestive of a protective role of the female sex hormones. Inflammatory processes have been implicated in the pathogenesis of cardio‐metabolic disease with human studies correlating metabolic disease acquisition or risk with levels of various inflammatory markers. Rodent studies employing genetic modifications or novel pharmacological approaches have provided mechanistic insight into the role of these inflammatory mediators. Sex differences impact inflammatory processes and the subsequent biological response. As a consequence, this may affect how inflammation alters metabolic processes between the sexes. Recently, some of our work in the field of inflammatory genes and metabolic control identified a sexual dimorphism in a preclinical model and caused us to question the frequency and scale of such findings in the literature. This review concentrates on inflammatory‐related signalling in relation to obesity, insulin resistance, and type 2 diabetes and highlights the differences observed between males and females. Differences in the activation and signalling of various inflammatory genes and proteins present another reason why studying both male and female patients or animals is important in the context of understanding and finding therapeutics for metabolic‐related disease. LINKED ARTICLES: This article is part of a themed section on The Importance of Sex Differences in Pharmacology Research. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.21/issuetoc